Application of polymerase chain reaction (PCR) in parasitology - TRIVIZAKI (Σ. ΤΡΙΒΙΖΑΚΗ) S.; THEODOROPOULOS (Γ. ΘΕΟΔΩΡΟΠΟΥΛΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The method of polymerase chain reaction (PCR) is applied for parasite identification, for studying genetic diversity between phylums, families and species of parasites, as well as for the diagnosis and epidemiological study of parasitic diseases. The biggest advantage of PCR is its higher sensitivity in comparison to other classical indirect diagnostic methods.